2021
DOI: 10.1038/s41396-021-01002-z
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary origin and ecological implication of a unique nif island in free-living Bradyrhizobium lineages

Abstract: The alphaproteobacterial genus Bradyrhizobium has been best known as N2-fixing members that nodulate legumes, supported by the nif and nod gene clusters. Recent environmental surveys show that Bradyrhizobium represents one of the most abundant free-living bacterial lineages in the world’s soils. However, our understanding of Bradyrhizobium comes largely from symbiotic members, biasing the current knowledge of their ecology and evolution. Here, we report the genomes of 88 Bradyrhizobium strains derived from div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…The increased abundance in bulk soils of nosZ I OTUs classified as Bradyrhizobium , a genus shown to be common in endophytic bacterial communities of multiple barley cultivars (Yang et al 2017 ), is also the most dominant bacterial lineage in soils throughout the world (Delgado-Baquerizo et al 2018 ). They have large genomes encoding a vast diversity of functions—including denitrification—that allow them to persist as free-living diazotrophs in oligotrophic conditions (Poole et al 2018 , Tao et al 2021 ). Oligotrophic conditions in bulk soil may also explain the greater abundance of nosZ II OTUs classified as Chloroflexi and Gemmatimonadetes, which in a recent meta-study have been shown to be depleted in the rhizosphere compared to bulk soil (Ling et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increased abundance in bulk soils of nosZ I OTUs classified as Bradyrhizobium , a genus shown to be common in endophytic bacterial communities of multiple barley cultivars (Yang et al 2017 ), is also the most dominant bacterial lineage in soils throughout the world (Delgado-Baquerizo et al 2018 ). They have large genomes encoding a vast diversity of functions—including denitrification—that allow them to persist as free-living diazotrophs in oligotrophic conditions (Poole et al 2018 , Tao et al 2021 ). Oligotrophic conditions in bulk soil may also explain the greater abundance of nosZ II OTUs classified as Chloroflexi and Gemmatimonadetes, which in a recent meta-study have been shown to be depleted in the rhizosphere compared to bulk soil (Ling et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within the biofilm, a high abundance of potentially diazotrophic bacteria, i.e., members from the order Rhizobiales (relative abundance of 15%, Figure 2 ), were detected. These bacteria included Bradyrhizobium , Mesorhizobium , and Methylobacterium which may aerobically fix nitrogen in a free-living life style [ 52 , 53 ] and contribute ammonia to the system, although some free-living non-diazotrophic rhizobia were reported recently [ 54 ]. Rhizobiales are also heterotrophs, so the autotrophic members, such as Thaumarchaeota and Nitrospirae, may provide organic matters in return.…”
Section: Resultsmentioning
confidence: 99%
“…In K. oboediens IMBG180, no structural genes of nitrogenase were found, and, to date, no experimental evidence of N-fixation by these species was reported. Free-living bacteria carry the nif -genes originated from symbiotic ancestors (carrying both nif- and nod -genes) ( Tao et al, 2021 ), and this transition is characterized by losses of symbiosis-related genes, most of which were in the symbiosis island. This loss probably occurred in K. oboediens , which now harbors only remnants of nif - and nod -genes clusters.…”
Section: Discussionmentioning
confidence: 99%